Исследование токсического действия фунгицида купроксата на Platymonas viridis Rouch. (Chlorophyta) - Кузьминова, Н.С. (Альгология, 2004)
Установлено токсическое действие фунгицида купроксата на культуру черноморской водоросли Platymonas viridis Rouch. (Chlorophyta). Добавление в среду 0,625; 1,25 и 2,5 мг/л пестицида сопровождалось увеличением численности клеток в период начальных этапов их развития (с 3-х по 12-е сутки). С добавлением пестицида уменьшалась оптическая плотность культуры в результате снижения численности клеток и повышалась ее теплопродукция в начале и в конце эксперимента по сравнению с контролем. рН среды изменялся незначительно. The toxic effects of cuproxat fungicide on the algal culture Platymonas viridis Rouch. (Chlorophyta) were determined. The addition of 0.625; 1.25, and 2.5 mg/L of pesticide into the medium was accompanied by an increase in cell quantity at early growth stages (from 3 to 12 days). The optical density of the culture decreased with the addition of pesticide, as indicated by a fall of cell quantity, and its heat productivity increased at the beginning and at the end of the experiment as compared to the control. The pH of the medium changed insignificantly.